2019
DOI: 10.1002/ldr.3383
|View full text |Cite
|
Sign up to set email alerts
|

Linking bacterial community to aggregate fractions with organic amendments in a sandy soil

Abstract: Soil aggregates provide microhabitats for microorganisms. However, the bacterial communities within various aggregate size fractions under organic amendments have rarely been evaluated especially in sandy soils. A field experiment involving addition of biogas residue (BR), pig manure (PM), biochar (BC), and straw (ST) of a sandy soil was performed to determine the structure of the bacterial community in aggregate size fractions by using high‐throughput sequencing. We found that organic amendments change soil a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…However, as the plots under study have been subjected to intensive farming activities since they were reclaimed, it was hard to acknowledge which changes in the key soil attributes which can be modified through both land reclamation and farming activities (Huo et al, 2018), is a relevant proxy to understand how a soil behaves from the physical (e.g., Lu & Likos, 2004), chemical (Saygin et al, 2017)), and biological standpoint (Chaganti & Crohn, 2015). In fact, the assessment of soil aggregates can shed light on the ability of soils to provide habitat to SMCs (Dai et al, 2019). We did not quantify the effect of land reclamation on soil aggregates, which is a limitation to the study, but we envisage that future work investigating the effect of land reclamation on key soil attributes should include soil aggregates in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the plots under study have been subjected to intensive farming activities since they were reclaimed, it was hard to acknowledge which changes in the key soil attributes which can be modified through both land reclamation and farming activities (Huo et al, 2018), is a relevant proxy to understand how a soil behaves from the physical (e.g., Lu & Likos, 2004), chemical (Saygin et al, 2017)), and biological standpoint (Chaganti & Crohn, 2015). In fact, the assessment of soil aggregates can shed light on the ability of soils to provide habitat to SMCs (Dai et al, 2019). We did not quantify the effect of land reclamation on soil aggregates, which is a limitation to the study, but we envisage that future work investigating the effect of land reclamation on key soil attributes should include soil aggregates in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The aggregate size class with high complexity of bacterial groups could provide biological buffering and thus was potentially stable after 39-year fertilizations. The less stable of network in smaller aggregates was due to the lack of physical protection for microbes among small particles (Dai et al, 2019). Meanwhile, the modularity in macroaggregate was significantly lower than that in smaller fractions (Table 1), indicating that macroaggregate had higher niche overlap than microaggregate and silt + clay fractions.…”
Section: Effects Of Soil Aggregate Sizes On Bacterial Community Patternsmentioning
confidence: 98%
“…Additionally, the numbers of biomarkers in macroaggregates and microaggregates were 60 and 59, respectively, which were evidently higher than in silt + clay (52 biomarkers). This indicated that the bacterial communities in silt + clay fractions were less sensitive to long-term fertilizations than those in larger aggregates (Yang et al, 2007;Dai et al, 2019). The lower vitality of bacterial communities in silt and clay fraction also explained why the nutrient turnover was much slower in the silt + clay aggregate size class than in larger aggregates.…”
Section: Effects Of Soil Aggregate Sizes On Bacterial Community Patternsmentioning
confidence: 99%
“…The SOM accumulation upon N fertilization occurs primarily in occluded particulate organic matter (Zak, Freedman, Upchurch, Steffens, & Kögel‐Knabner, ). Long‐term mineral and/or organic N fertilization facilitates C sequestration by increasing soil С input from larger plant biomass and manure (Dai et al, ; Liang et al, ; Zang, Qian, et al, ), and by reducing SOM decomposition (Liu et al, ; Xiao, Zang, Ge, et al, ; Xiao, Zang, Liu, et al, ). Organic N stimulates SOM decomposition more than mineral N (Chen et al, ) due to an increase of microbial activity and more necromass production (Liang et al, ).…”
Section: Introductionmentioning
confidence: 99%